Intrinsic connectivity network dynamics in PTSD during amygdala downregulation using real‐time fMRI neurofeedback: A preliminary analysis. Issue 11 (13th July 2018) - Nicholson, Andrew A.; Rabellino, Daniela; Densmore, Maria; Frewen, Paul A.; Paret, Christian; Kluetsch, Rosemarie; Schmahl, Christian; Théberge, Jean; Ros, Tomas; Neufeld, Richard W. J.; McKinnon, Margaret C.; Reiss, Jeffrey P.; et al.
Abstract: Posttraumatic stress disorder (PTSD) has been associated with a disturbance in neural intrinsic connectivity networks (ICN), including the central executive network (CEN), default mode network (DMN), and salience network (SN). Here, we conducted a preliminary investigation examining potential changes in ICN recruitment as a function of real‐time fMRI neurofeedback (rt‐fMRI‐NFB) during symptom provocation where we targeted the downregulation of neural response within the amygdala—a key region‐of‐interest in PTSD neuropathophysiology. Patients with PTSD ( n  = 14) completed three sessions of rt‐fMRI‐NFB with the following conditions: (a) regulate : decrease activation in the amygdala while processing personalized trauma words; (b) view : process trauma words while not attempting to regulate the amygdala; and (c) neutral : process neutral words. We found that recruitment of the left CEN increased over neurofeedback runs during the regulate condition, a finding supported by increased dlPFC activation during the regulate as compared to the view condition. In contrast, DMN task‐negative recruitment was stable during neurofeedback runs, albeit was the highest during view conditions and increased (normalized) during rest periods. Critically, SN recruitment was high for both the regulate and the view conditions, a finding potentially indicative of CEN modality switching, adaptive learning, and increasing threat/defense processing in PTSD. In conclusion, this study provides provocative, preliminary evidence that downregulation of the amygdala using rt‐fMRI‐NFB in PTSD is associated with dynamic changes in ICN, an effect similar to those observed using EEG modalities of neurofeedback.